2018
DOI: 10.1016/j.freeradbiomed.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and GPX4, a vital symbiosis

Abstract: Selenium has transitioned from an environmental poison and carcinogen to an essential micronutrient associated with a broad array of health promoting effects. These beneficial effects are now accepted to be linked to its incorporation into selenoproteins, a family of rare proteins utilizing a specialized translation machinery to integrate selenium in the form of selenocysteine. Despite this recognized role, much less is known regarding the actual role of selenium in these proteins. Here, we will provide the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 79 publications
2
72
0
1
Order By: Relevance
“…Strong GFAP staining in the cerebral cortex of two week old mice was also reported in a model of conditional deletion of the selenocysteinespecific tRNA using Camk2α-Cre and Trsp fl/fl transgenic mice [38]. As the selenoenzyme GPX4 is nowadays accepted to be (one of) the main target(s) of selenium particularly in brain [63], one can infer that many of the phenotypes provoked by tissue-specific deletion of Trsp are, in fact, caused by impaired GPX4 expression and activity [64]. In two models of neuron-specific GPX4 ablation, Ran's group then demonstrated the presence of neuroinflammation (as determined by staining against the microglia marker Iba1 (Ionized calcium binding adaptor molecule 1)) in the lumbar spinal cord region of dying motor neurons and in the CA1 region of the hippocampus [35,36].…”
Section: Signs Of Necroinflammation In Ferroptotic Tissuementioning
confidence: 84%
“…Strong GFAP staining in the cerebral cortex of two week old mice was also reported in a model of conditional deletion of the selenocysteinespecific tRNA using Camk2α-Cre and Trsp fl/fl transgenic mice [38]. As the selenoenzyme GPX4 is nowadays accepted to be (one of) the main target(s) of selenium particularly in brain [63], one can infer that many of the phenotypes provoked by tissue-specific deletion of Trsp are, in fact, caused by impaired GPX4 expression and activity [64]. In two models of neuron-specific GPX4 ablation, Ran's group then demonstrated the presence of neuroinflammation (as determined by staining against the microglia marker Iba1 (Ionized calcium binding adaptor molecule 1)) in the lumbar spinal cord region of dying motor neurons and in the CA1 region of the hippocampus [35,36].…”
Section: Signs Of Necroinflammation In Ferroptotic Tissuementioning
confidence: 84%
“…Therefore, ferroptosis can be induced by RSL3, and FINO 2 treatment effects similar to that of inhibited GPX4 inactivation. On the other hand, selenium (Se) was the first extensively reported key regulator of GPX4 activity (Ingold et al, 2015(Ingold et al, , 2018Angeli and Conrad, 2018;Alim et al, 2019). Alim et al (2019) reported that pharmacological Se supplementation effectively inhibits GPX4-dependent ferroptotic death, as well as cell death induced by excitotoxicity or ER stress, and can inhibit cell death and improve cell function when administrated after hemorrhagic or ischemic stroke.…”
Section: Gpx4-gsh-cysteine Axismentioning
confidence: 99%
“…SLC7A11 is highly expressed in a variety of tumors; by increasing cystine uptake it leads to increased intracellular GPX4 synthesis, reduced intracellular oxidative stress and the suppression of ferroptosis, thereby promoting tumor growth (60,61). GPX4 is a GSH-dependent enzyme, and selenocysteine, which is one of the amino acids in the active center of GPX4, can be inserted into GPX4 through selenocysteine transfer RNA (tRNA) (62,63). In addition, the maturation of selenocysteine tRNA may also be regulated by the mevalonate pathway to act on GPX4 (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…GPX4 is a GSH-dependent enzyme, and selenocysteine, which is one of the amino acids in the active center of GPX4, can be inserted into GPX4 through selenocysteine transfer RNA (tRNA) (62,63). In addition, the maturation of selenocysteine tRNA may also be regulated by the mevalonate pathway to act on GPX4 (62,63). GSH and selenocysteine both regulate the occurrence of ferroptosis in cells by affecting GPX4.…”
Section: Discussionmentioning
confidence: 99%